Comparison of greenhouse gas fluxes from tropical forests and oil palm plantations on mineral soil - Drewer, Julia; Leduning, Melissa M.; Griffiths, Robert I.; Goodall, Tim; Levy, Peter E.; Cowan, Nicholas; Comynn-Platt, Edward; Hayman, Garry; Sentian, Justin; Majalap, Noreen; Skiba, Ute M. (Biogeosciences, 2021)
In Southeast Asia, oil palm (OP) plantations have largely replaced tropical forests. The impact of this shift in land use on greenhouse gas (GHG) fluxes remains highly uncertain, mainly due to a relatively small pool of available data. The aim of this study is to quantify differences of nitrous oxide (N2O) and methane (CH4) fluxes as well as soil carbon dioxide (CO2) respiration rates from logged forests, oil palm plantations of different ages, and an adjacent small riparian area. Nitrous oxide fluxes are the focus of this study, as these emissions are expected to increase significantly due to the nitrogen (N) fertilizer application in the plantations. This study was conducted in the SAFE (Stability of Altered Forest Ecosystems) landscape in Malaysian Borneo (Sabah) with measurements every 2 months over a 2-year period. GHG fluxes were measured by static chambers together with key soil physicochemical parameters and microbial biodiversity. At all sites, N2O fluxes were spatially and temporally highly variable. On average the largest fluxes (incl. 95 % CI) were measured from OP plantations (45.1 (24.0–78.5) µg m−2 h−1 N2O-N), slightly smaller fluxes from the riparian area (29.4 (2.8–84.7) µg m−2 h−1 N2O-N), and the smallest fluxes from logged forests (16.0 (4.0–36.3) µg m−2 h−1 N2O-N). Methane fluxes were generally small (mean ± SD): −2.6 ± 17.2 µg CH4-C m−2 h−1 for OP and 1.3 ± 12.6 µg CH4-C m−2 h−1 for riparian, with the range of measured CH4 fluxes being largest in logged forests (2.2 ± 48.3 µg CH4-C m−2 h−1). Soil respiration rates were larger from riparian areas (157.7 ± 106 mg m−2 h−1 CO2-C) and logged forests (137.4 ± 95 mg m−2 h−1 CO2-C) than OP plantations (93.3 ± 70 mg m−2 h−1 CO2-C) as a result of larger amounts of decomposing leaf litter. Microbial communities were distinctly different between the different land-use types and sites. Bacterial communities were linked to soil pH, and fungal and eukaryotic communities were linked to land use. Despite measuring a large number of environmental parameters, mixed models could only explain up to 17 % of the variance of measured fluxes for N2O, 3 % of CH4, and 25 % of soil respiration. Scaling up measured N2O fluxes to Sabah using land areas for forest and OP resulted in emissions increasing from 7.6 Mt (95 % confidence interval, −3.0–22.3 Mt) yr−1 in 1973 to 11.4 Mt (0.2–28.6 Mt) yr−1 in 2015 due to the increasing area of forest converted to OP plantations over the last ∼ 40 years.